2012 First National Conference for Engineering Sciences (FNCES 2012) 2012
DOI: 10.1109/nces.2012.6543527
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment in ESL writing classroom

Abstract: Based on the Socio-cultural Theory and its key notion of Zone of Proximal Development, this study constructs a Dynamic Assessment writing Framework, which integrates three stages of writing process into the pre-writing -mediation -post-writing dynamic assessment model. The thesis conducts a detailed description of the implementation of the writing process framework into the dialogue-centered ESL writing classroom instruction in a hope of providing ESL teachers with a practical and easily and effectively manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Their results also showed that the way feedback is provided in interactionist approach, avoids learners lucky guesses when they try to correct themselves, so their improvement would be more than those treated traditionally. One point to be kept in mind is that both in Miao and Lv (2013) and the present study, all the participants whether in control or experimental group had improvement but the amount of improvement in similar conditions is more important.…”
Section: Data Analysis and Discussionmentioning
confidence: 67%
“…Their results also showed that the way feedback is provided in interactionist approach, avoids learners lucky guesses when they try to correct themselves, so their improvement would be more than those treated traditionally. One point to be kept in mind is that both in Miao and Lv (2013) and the present study, all the participants whether in control or experimental group had improvement but the amount of improvement in similar conditions is more important.…”
Section: Data Analysis and Discussionmentioning
confidence: 67%